Biostimulant Capacity of an Enzymatic Extract From Rice Bran Against Ozone-Induced Damage in Capsicum annum - Macias-Benitez, Sandra; Navarro-Torre, Salvadora; Caballero, Pablo; Martín, Luis; Revilla, Elisa; Castaño, Angélica; Parrado, Juan (Frontiers in Plant Science, 2021)
Ozone is a destructive pollutant, damaging crops and decreasing crop yield. Therefore, there is great interest in finding strategies to alleviate ozone-induced crop losses. In plants, ozone enters leaves through the stomata and is immediately degraded into reactive oxygen species (ROS), producing ROS stress in plants. ROS stress can be controlled by ROS-scavenging systems that include enzymatic or non-enzymatic mechanisms. Our research group has developed a product from rice bran, a by-product of rice milling which has bioactive molecules that act as an antioxidant compound. This product is a water-soluble rice bran enzymatic extract (RBEE) which preserves all the properties and improves the solubility of proteins and the antioxidant components of rice bran. In previous works, the beneficial properties of RBEE have been demonstrated in animals. However, to date, RBEE has not been used as a protective agent against oxidative damage in agricultural fields. The main goal of this study was to investigate the ability of RBEE to be used as a biostimulant by preventing oxidative damage in plants, after ozone exposure. To perform this investigation, pepper plants (Capsicum annuum) exposed to ozone were treated with RBEE. RBEE protected the ozone-induced damage, as revealed by net photosynthetic rate and the content of photosynthetic pigments. RBEE also decreased the induction of antioxidant enzyme activities in leaves (catalase, superoxide dismutase, and ascorbate peroxidase) due to ozone exposure. ROS generation is a common consequence of diverse cellular traumas that also activate the mitogen-activated protein kinase (MAPK) cascade. Thus, it is known that the ozone damages are triggered by the MAPK cascade. To examine the involvement of the MAPK cascade in the ozone damage CaMPK6-1, CaMPK6-2, and CaMKK5 genes were analysed by qRT-PCR. The results showed the involvement of the MAPK pathway in both, not only in ozone damage but especially in its protection by RBEE. Taken together, these results support that RBEE protects plants against ozone exposure and its use as a new biostimulant could be proposed.